Barnacle Geese in Western Scotland, February 1957 - Boyd, Hugh; Radford, John (Wildfowl, 1957)
The present status of the Barnacle Goose (Branta leucopsis) is of particular interest, because this species, of which a large proportion winter in the British Isles, seems to have decreased seriously in numbers during this century. But it has hitherto been impossible to attempt a census of the wintering population, because this is scattered over a large number of islands off the coasts of Ireland and the west of Scotland, and frequents only a few mainland localities (although the flocks found on the mainland are comparatively large ones). In order to discover whether the use of an aircraft for making a census of the Barnacle Goose was practicable, the writers spent the period 11-24 February 1957 in searching parts of the mainland coast of the west of Scotland and most of the Inner and Outer Hebrides. The completeness of the cover achieved was a pleasant surprise, in view of the potential hazards of flying in this area in winter.